Temperature heat detector / Ahmad Syakirin Ismail @ Rosdi, Muhammad Amir Ridhwan Abdullah and Raziah Abdul Rahman - Ismail @ Rosdi, Ahmad Syakirin; Abdullah, Muhammad Amir Ridhwan; Abdul Rahman, Raziah (2010)
Nowadays, there are many security devices or instrument that involved in security or alarm application. Although simple alarm just triggered the sound, or some upgraded feature that some of the alarm can cut off the small fire, those alarm at least had decrease the number of damages that cause of fire. Most alarms normally had only one feature in ones alarm. For example fire alarm responds to change in ambient temperature and smoke and if the ambient temperature rises above a predetermined threshold, an alarm signal is triggered. As the result, water will spill out or fan will spin. Just think how it could be if a security alarm can triggered an alarm sound, reduce the temperature by using vitalization fan and spill out the water? Considering all the aspect that involved in alarm system, we decided to do a project based on alarm. So, we decided to do a heat detector circuit. However, this alarm only triggered an alarm when there is a change in ambient temperature. Consequently, we will upgrade this ordinary heat detector by adding the vitalization fan and water as additional feature that will lower down the heat and get rid off the smoke.